2017
DOI: 10.1108/mip-04-2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

The effects of regulatory focus and mixed valence imagery and analytical attributes on product decisions

Abstract: Purpose-This paper investigates the effects of regulatory focus (promotion vs. prevention) and mixed valence attributes (positive imagery and negative analytical vs. negative imagery and positive analytical) on consumers' evaluation and purchase intention for a product. Design/methodology/approach-A pre-test followed by a single between subject's experiment was conducted to test the major hypotheses in the study. Findings-Results show that promotion (prevention) focus prefer the product when it is described in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…A recent study by Das (2015) that examined the effects of regulatory focus on impulsiveness and loyalty also found interesting linkages indicating that promotion focus is positively related to impulsiveness and prevention focus is negatively associated with impulsiveness. In a similar vein, another recent study by Roy (2017) showed that individuals with a promotion orientation focus more on positive imagery attributes in their product decisions, whereas those with a prevention orientation focus prefer analytical ones. In all of these studies, promotion focus has been shown to either have positive relationships with hedonic-related factors or focus more on positive outcomes like perceived benefits.…”
Section: Regulatory Focus Theorymentioning
confidence: 80%
See 1 more Smart Citation
“…A recent study by Das (2015) that examined the effects of regulatory focus on impulsiveness and loyalty also found interesting linkages indicating that promotion focus is positively related to impulsiveness and prevention focus is negatively associated with impulsiveness. In a similar vein, another recent study by Roy (2017) showed that individuals with a promotion orientation focus more on positive imagery attributes in their product decisions, whereas those with a prevention orientation focus prefer analytical ones. In all of these studies, promotion focus has been shown to either have positive relationships with hedonic-related factors or focus more on positive outcomes like perceived benefits.…”
Section: Regulatory Focus Theorymentioning
confidence: 80%
“…Consumer behavior scholars have recognized the importance of individuals' psychological differences in a consumption situation and have attempted to use the RFT to more thoroughly examine underlying mechanisms (Das, 2015;Hassenzahl et al, 2008;Pham and Higgins, 2005;Roy, 2017;Roy and Ng, 2012;Trudel et al, 2012;Yeo and Park, 2006). For example, Yeo and Park (2006) studied regulatory focus fit by testing how participants reacted to a brand extension strategy when the extension was similar versus dissimilar to the original brand.…”
Section: Regulatory Focus Theorymentioning
confidence: 99%
“…However, when promotion-focused people are sad, they are more likely to be sensitive to future losses ( Lench et al, 2011 ). In contrast, prevention-focused individuals with high risk aversions tend to decrease their reliance on emotions but increase their reliance on analytical processes ( Friedman and Förster, 2000 ; Roy, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, when promotionfocused people are sad, they are more likely to be sensitive to future losses (Lench et al, 2011). In contrast, prevention-focused individuals with high risk aversions tend to decrease their reliance on emotions but increase their reliance on analytical processes (Friedman and Förster, 2000;Roy, 2017). The objective of experiment 3 was to investigate the interactive effect of salient sources of emotions and regulatory focus on information preferences.…”
Section: Summary Of Findings and Implicationsmentioning
confidence: 99%
“…De acordo com as teorias da psicológica clássica sobre motivação, feedback de sucesso levanta as expectativas de resultados e induz ou mantém a motivação de aproximação, enquanto que o feedback de falha reduz as expectativas de resultados e induz ou mantém a motivação de afastamento (Atkinson, 1964;Föster et al, 2001). De acordo com Os modelos positivos, os indivíduos que tenham alcançado um sucesso extraordinário, inspiram outras pessoas a buscarem uma excelência similar (Lockwood, Jordan & Kunda, 2002 foco em promoção seja substituído quando é necessária uma vigilância da situação (Larsen, 2004;Roy, 2017).…”
Section: Foco Regulatóriounclassified